Pengaruh Model Pembelajaran Berdasarkan Masalah Berbasis Budaya terhadap Kemampuan Berpikir Komputasi di SMP 23 Medan - Zulmawati Zulmawati; Dian Arisetya (Journal on Education, 2024)
This research aims to find out whether there are differences in students' computational thinking with conventional problem-based learning models based on Batak culture (PBM-B3). This research is a quasi-experimental research. The model used in this research is a problem-based learning model based on Batak culture with research subjects of 46 class VIII students at SMP Advent 23 Medan. The object of this research is students' computational thinking abilities. The results of the research show that there are differences in computational thinking abilities between students who were given learning based on problems based on Batak culture and students who were given direct learning. Descriptively, the post-test average for experiment 1 was 86.96, while experiment 2 was 78.04. Based on the normalized index obtained, it was found that in trial II there was an increase in students' computational thinking abilities by 0.25.